Exploration of Students' Problem Solving Ability in View of Self-Regulated Learning on the Topic of Two Variable Linear Equation Systems - Abdul Karim; Tian Abdul Aziz (STKIP Singkawang, 2023)
There are factors that influence the success of mathematical solution to problem abilities namely is self-regulated learning. This’s an internal factor that must be possessed by students which is still not optimal and needs to be studied. This study aims to explore and describe solving mathematical problems in SPLDV material, namely the elimination method and the substitution method. The population of class VIII students at modern female Islamic boarding school At-taqwa Bogor are all female students. Mixed method is the step used in this study with a concurrent embedded design. Experimental class VIII.C and 6 subjects were selected, divided into 2 student cognition of regulation, 2 students Motivation of regulation, 2 students Behavior of regulation. Data collection was carried out by tests, questionnaires and interviews. The results of the study; 1) The MMP learning model is more successful in the ability to solve problems in the KKM score; 2) The average value of the problem-solving ability test in the MMP class is better than direct learning; 3) the factor of self-regulated learning is concluded that; (a) students' problem solving skills with very good cognitive regulation; (b) Problem solving skills with good predicate motivational regulation and sufficient checking of answers; (c) The ability of students with affective regulation in the three steps is quite sufficient.